Analysis of Waste Bank Implementation and Zero Waste Program on Changes in Community Behavior and Waste Volume in Bandung City - Melawati, Fitri (Westscience Press, 2025)
Municipal waste is a serious concern in cities, and there should be efficient programs to minimize waste quantity and promote sustainable practices. This study examines the impact of Waste Bank Implementation (WBI) and the Zero Waste Program (ZWP) on Changes in Community Behavior (CCB) and Waste Volume (WVO) in Bandung, Indonesia, using quantitative analysis with 220 samples collected from a Likert-scale (1-5) survey and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The results reveal that ZWP has the greatest impact on behavior change and waste reduction, which speaks volumes about the effectiveness of education, policy, and awareness campaigns, while WBI affects both behavior change and waste reduction but to a smaller degree than ZWP. The results thus reveal that although waste banks are accountable for waste reduction, policy-based interventions such as the Zero Waste Program are more effective in maintaining long-term sustainability. Therefore, a combined approach involving financial incentives, education campaigns, and sound waste policy is required for sustainable urban waste management, and future studies should draw qualitative results on behavioral drivers and compare across cities to ensure the highest generalizability.